A comprehensive analysis of blockchain-based cryptocurrency mining impact on energy consumption - Islam, Md Rafiqul; Rashid, Muhammad Mahbubur; Rahman, Mohammed Ataur; Mohamad, Muslim Har Sani; Embong, Abd Halim (Science and Information Organization, 2022)
Blockchain already has gained popularity due to its highly secured network and same time enormous computational power consumption has become an undifferentiated debate among the users. A Blockchain network is reliable, secure, transparent, and immutable where the transactions cannot be reversed between sender and receiver. Blockchain technology is not only used for mining cryptocurrency, it has other applications in different sectors like agriculture, education, insurance, etc., but the noticeable concern is still energy consumption. On the other hand, there is a significant impact on the environment due to the use of excessive energy for mining cryptocurrency which releases more carbon dioxide (CO2) in nature. The Proof-of-Work (PoW) algorithm is used for mining ‘Bitcoin’ which is consumed enormous computational power. However, an alternative solution like Proof-of-Stake (PoS) consensus protocol has been proposed to use instead of the Proof-of-Work algorithm for mining cryptocurrencies which is capable to reduce the significant amount of energy consumption. Not only that, but the use of renewable energy can also be an alternate option to use the Proof-of-Work algorithm for mining cryptocurrencies which is environment friendly. This paper aims to highlight blockchain technology, the energy consumption and impact on the environment, energy reducing method by using PoS consensus protocol instead of using the